DENTIFICATION OF LAND MOVEMENTS BASED ON GEOGRAPHIC INFORMATION SYSTEMS AND DIPOLE-DIPOLE CONFIGURATION RESISTIVITY METHOD FOR LANDSLIDE DISASTER MITIGATION IN THE SELOHARJO, PUNDONG, BANTUL, YOGYAKARTA SPECIAL REGIONS - Wikranta Setiawan, Ketut Arya; Nurkhamim, Nurkhamim; Winarno, Eddy (Jurnal Teknologi Pertambangan, 2025)
Seloharjo Village, Pundong, Bantul is an area that has geographical conditions in the form of mountains and hills, making the area prone to landslides. Landslides are geological disasters where masses of soil and rock move down slopes which are influenced by landslide parameters in the form of rainfall, slope, vegetation, seismicity and geology. A slip plane is a rock layer that has relatively lower permeability compared to the layer above it so that it can become a plane for the movement of soil and rock masses above it. Identification of the landslide slip plane was carried out using the dipole-dipole configuration geoelectric method with a path length of 260 m on track 1 and 220 m on track 2. The results of geoelectrical measurements show high subsurface resistivity values with a value range of 158 - 280 Ωm which is thought to be limestone material as a land sliding area and low resistivity values with a value range of 5 - 150 Ωm which is a layer of alluvial sediment as landslide material. Alluvial deposits in the research area become landslide material with the sliding surface being a layer of limestone, because the permeability value of limestone is smaller than that of alluvial deposits. Based on a review of the geographic information system in the form of a landslide susceptibility map obtained from the parameters of landslide events, it shows that the research area has a high rainfall value of 2,629 mm/year, a slope slope of 25 - 45%, vegetation with strong roots and dense leaves, level high earthquake susceptibility, and geological conditions in the form of a slip plane in the direction of the slope, from these parameters the research area has a high level of landslide susceptibility. On track 1, the slope direction of the slip plane is found to be in the same direction as the slope of the slope with high landslide potential.  Meanwhile, on route 2, the direction of the slope of the slip surface is opposite to the direction of the slope of the slope with low landslide potential. The results of the integration of geophysical data with GIS show that route 1 has a high landslide potential in terms of the analysis of the slip plane in the direction of the slope as well as the geographic information system which shows that the research area has a high level of landslide proneness so that mitigation is needed in the form of creating an evacuation route.